Model Pengembangan Leadership Style Dalam Pendidikan Tinggi - Deni Surapto; Rahmaddian Rahmaddian (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
The dynamics of the era of disruption have an impact on the industrial world and the business world, which requires companies to adapt to the environment. The speed of information technology creates intense competition and competition among companies to gain market share and become a market leader. The Open University (UT) is a higher education institution that has been implementing distance learning since 1984. To facilitate its services, UT has a Distance Learning Program Unit (UPBJJ) which is a UT technical implementation unit spread across every province. It has the task of carrying out administrative and public relations activities as well as promotion. Carry out learning assistance service activities and teaching material services which include implementing tutorials and extracurriculars, developing, fostering, and carrying out collaborations with various agencies. This requires human resources to perform. Agile leadership is a leadership style that seeks to remove obstacles to success so that employees can be more effective and productive. The research methodology used a quantitative approach, the population in the study was around 2,300 UT employees with a sample of 130 employees through a positive random sampling approach, the instrument was a 5-scale questionnaire, ranging from negative statements that strongly disagree to positive statements that strongly agree. The results showed that AL had a significant positive effect on Work Stress, WS had a significant positive effect on Job satisfaction, Job Satisfaction had a positive significant effect on Innovation, AL had a positive effect on Employee Performance, WS had a positive effect on Employee Performance, Job satisfaction had a positive effect on Employee Performance, Innovation employees have a positive effect on employee performance.Keywords: Agile Leadership, Job Stress, Job Satisfaction on Employee Performance